A calcium polycarbophil oral solid preparation and a preparation method thereof
Patent Information
- Application Number
- CN202611165138.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-03
- Publication Date
- 2026-10-23
AI Technical Summary
1.本发明通过聚卡波非钙与预胶化淀粉形成多孔桥联颗粒,使预胶化淀粉在颗粒表面形成可调覆盖,既减少聚卡波非钙细粉直接参与混合造成的流动阻滞,又避免颗粒过度长大导致辅料分布不均,从而有利于提高制剂加工稳定性和单位剂量一致性。
Smart Images

Figure CN122954739A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of oral solid dosage forms, specifically to a polycarboxymethyl calcium oral solid dosage form and its preparation method. Background Technology
[0002] In scenarios involving intestinal regulation, long-term medication management, and portable administration, polycarboxymethyl calcium oral solid dosage forms need to simultaneously meet requirements such as high drug loading, processability, dosage consistency, and post-administration disintegration and dispersion. These formulations typically use a high proportion of polycarboxymethyl calcium as the main component. The raw material particles exhibit processing characteristics such as hygroscopicity, swelling, density variations, and insufficient powder flowability. Simply pursuing larger particles and a lower proportion of fine powder, while beneficial for improving flow and tableting stability, may lead to uneven spatial distribution of particles and excipients during mixing, transfer, and tableting. Conversely, simply increasing the fine powder gradation to improve mixing uniformity can easily result in bridging, adhesion, dust generation, and flow hindrance. Meanwhile, different dosage forms, such as tablets, capsule-filled granules, and granules, also need to consider mechanical strength, disintegration performance, storage stability, and batch-to-batch consistency. Therefore, achieving a reproducible balance between particle structure, excipients, and process window is a crucial technical direction in the development of this type of oral solid dosage form.
[0003] Existing technologies have explored various formulations and processes for polycarboxymethyl calcium solid dosage forms. For example, Chinese patent CN112704664A discloses a polycarboxymethyl calcium tablet and its preparation method. The background section mentions existing solutions related to polycarboxymethyl calcium compositions, disintegrants, fillers, lubricants, and solubilizers, but concerns remain regarding tablet disintegration, bioavailability, and medication adherence. While these solutions can improve some properties through disintegration promotion, hydrophilic matrices, or direct compression, coupling limitations still exist between particle size distribution, surface bridging, excipient stacking behavior, and compression strength in high-content polycarboxymethyl calcium systems. In particular, when increasing structural strength to enhance particle bridging and compaction, water ingress and particle dispersion channels may be restricted; conversely, enhancing looseness or adding disintegrant components to improve disintegration and dispersion may weaken tablet abrasion resistance and transport stability. Therefore, a formulation and preparation method that can simultaneously coordinate particle flow, dosage uniformity, mechanical strength, and disintegration performance is still needed. Summary of the Invention
[0004] The purpose of this invention is to provide a polycarboxyfil calcium oral solid dosage form and its preparation method, thereby solving the problem that it is difficult to balance processing flowability, dosage uniformity, mechanical strength and disintegration performance in current high-content polycarboxyfil calcium oral solid dosage forms.
[0005] This invention forms porous bridged particles by combining polycarboxymethyl calcium with pregelatinized starch, and controls the addition of excipients and wet granulation conditions to ensure that the particle size distribution is not too dense and maintains flowability, and that the tablet structure is not too loose and maintains strength, thereby achieving a synergistic balance between processing stability and post-administration dispersibility.
[0006] To achieve the above objectives, the present invention provides the following technical solution: A polycarboxycalcium oral solid dosage form comprises polycarboxycalcium-pregelatinized starch porous bridged particles, microcrystalline cellulose, colloidal silica, and magnesium stearate; The polycarboxylic acid calcium-pregelatinized starch porous bridging particles include polycarboxylic acid calcium and pregelatinized starch. In the polycarboxymethyl calcium-pregelatinized starch porous bridging particles, the mass ratio of polycarboxymethyl calcium to pregelatinized starch is 100:8–25. In the aforementioned polycarboxymethyl calcium oral solid dosage form, the content of polycarboxymethyl calcium is 55.00–78.00 wt% based on the total mass of the polycarboxymethyl calcium oral solid dosage form.
[0007] Furthermore, the D50 of the polycarboxylic acid calcium-pregelatinized starch porous bridged particles is 180–450 μm, and the projected area coverage of the pregelatinized starch on the surface of the polycarboxylic acid calcium particles is 30.00–75.00%.
[0008] Furthermore, the polycarboxylated non-calcium-pregelatinized starch porous bridging particles are prepared through the following steps: A1. Raw material preparation: Take 100 parts by weight of polycarboxymethyl calcium and 8–25 parts by weight of pregelatinized starch; A2. Dry mixing: The polycarboxymethyl calcium is mixed with the portion of the pregelatinized starch used for dry mixing to obtain a dry-mixed powder; A3. Wet bridging granulation: Granulation solution is added to the dry-mixed powder to granulate it and wet granules are obtained. A4. Post-processing: The wet granules are dried and granulated to obtain the polycarboxylic acid calcium-pregelatinized starch porous bridged granules.
[0009] Furthermore, in step A2, the polycarboxymethyl calcium and the portion of the pregelatinized starch used for dry mixing are mixed in an air atmosphere for 5–15 min; In step A3, the granulation conditions are 20–35℃ and normal pressure, and the granulation time is 3–8 min. In step A4, the wet granules are dried at 45–65°C until the weight loss is 1.50–4.00 wt%, and then granulated through a 0.80–1.50 mm sieve. The proportion of fine powder smaller than 75 μm in the obtained polycarboxylated calcium-pregelatinized starch porous bridged particles was 2.00–15.00 wt%.
[0010] Further, the granulation solution in step A3 is a pregelatinized starch aqueous dispersion, which is obtained by dispersing 5–20 parts by weight of the pregelatinized starch and 80–95 parts by weight of purified water at 20–35°C for 5–20 min. The pH value of the pregelatinized starch aqueous dispersion is 5.0–7.5. The portion of the pregelatinized starch not used to prepare the pregelatinized starch aqueous dispersion is mixed with the polycarboxymethyl calcium in step A2, and all of the pregelatinized starch aqueous dispersion is added to the dry-mixed powder for wet bridging granulation to obtain wet granules, which are then sent to the drying step.
[0011] Further, in step A3, the granulation solution is purified water, and all the pregelatinized starch is mixed with the polycarboxymethyl phosphate in step A2. The total amount of purified water added is 8.00–18.00 wt% of the total mass of the polycarboxymethyl phosphate and the pregelatinized starch. The purified water is added in several portions, with each addition being 2.00–6.00 wt% of the total mass of the polycarboxymethyl phosphate and the pregelatinized starch. The granulation endpoint is defined as a free fine powder ratio of less than 75 μm, measured after drying of the sampled wet granules, being 2.00–15.00 wt%.
[0012] Furthermore, in step A4, the drying is carried out using fluidized bed drying, with an inlet air temperature of 50–65℃ and an outlet air temperature of 35–50℃, until the drying loss is 1.50–4.00 wt%.
[0013] Furthermore, the content of microcrystalline cellulose in the polycarboxymethyl calcium oral solid dosage form is 5.00–20.00 wt%, the content of colloidal silica in the polycarboxymethyl calcium oral solid dosage form is 0.20–1.00 wt%, and the content of magnesium stearate in the polycarboxymethyl calcium oral solid dosage form is 0.30–1.50 wt%, and the total content of polycarboxymethyl calcium, pregelatinized starch, microcrystalline cellulose, colloidal silica, and magnesium stearate, based on the total mass of the polycarboxymethyl calcium oral solid dosage form, is not greater than 100 wt%.
[0014] Furthermore, the polycarboxymethyl cellulose oral solid dosage form further includes croscarmellose sodium, wherein the content of croscarmellose sodium in the polycarboxymethyl cellulose oral solid dosage form is 0.50–6.00 wt%, and the total content of polycarboxymethyl cellulose, pregelatinized starch, microcrystalline cellulose, colloidal silica, magnesium stearate and croscarmellose sodium, based on the total mass of the polycarboxymethyl cellulose oral solid dosage form, is not greater than 100 wt%.
[0015] Furthermore, the polycarboxymethyl calcium oral solid dosage form is a tablet, capsule-filled granule, or granule; when the polycarboxymethyl calcium oral solid dosage form is a tablet, the content of polycarboxymethyl calcium in a single tablet is 300–800 mg.
[0016] As a concept of this invention, the present invention employs a design that matches polycarbohydrate-calcium pregelatinized starch porous bridging particles with excipients, primarily to achieve a synergistic balance between processing flowability and dosage uniformity, as well as between mechanical strength and disintegration performance. In existing technologies, to improve processing flowability, particle size is typically increased and the proportion of fine powder is reduced; however, the packing differences between particles and excipients increase dosage fluctuations. Conversely, to improve dosage uniformity, a finer gradation or a more uniform particle size distribution is required, which introduces flow hindrance and adhesion risks. Simultaneously, to improve mechanical strength, bridging and compaction are typically enhanced, but moisture penetration and particle dispersion are limited; to improve disintegration, structural density must be reduced, weakening abrasion resistance. This invention, through pregelatinized starch bridging coverage, particle size control, fine powder ratio adjustment, and synergistic distribution of excipients, mitigates these two types of side effects, achieving a comprehensive and feasible state suitable for oral solid dosage forms.
[0017] This invention also discloses a method for preparing polycarboxymethyl calcium oral solid dosage form, comprising the following steps: S1. Provide polycarbohydrate calcium-pregelatinized starch porous bridged particles obtained in steps A1 to A4; S2. Mix the polycarboxymethyl calcium-pregelatinized starch porous bridging particles with microcrystalline cellulose and colloidal silica for 5–20 min, then add magnesium stearate and mix for 2–6 min to obtain the total mixture; S3. Compress the total mixture into tablets, capsules, or dispense to obtain the polycarboxymethyl calcium oral solid dosage form.
[0018] Furthermore, in step S1, the polycarboxylic acid calcium-pregelatinized starch porous bridging particles are prepared using steps A1 to A4, and in step A2, the polycarboxylic acid calcium and the portion of the pregelatinized starch used for dry mixing are first mixed at a low speed for 5–10 min, and then mixed at a high shear rate for 1–5 min.
[0019] Furthermore, in step S2, the amount of colloidal silica added is 0.20–1.00 wt% of the total mixture, and the amount of magnesium stearate added is 0.30–1.50 wt% of the total mixture.
[0020] Furthermore, when step S3 is tableting, the main tableting pressure is 6–18 kN, the resulting tablets have a friability of 0.10–1.00% and a disintegration time of 5–18 min.
[0021] Furthermore, in the wet bridging granulation process, wet particles are taken out from the granulation system and sieved through a sieve with a mesh size of 0.80–1.50 mm. The wet particles that pass through the sieve are taken as wet particles to be dried. The wet particles to be dried are dried and sieved at 75 μm. The proportion of free fine powder is calculated according to the ratio of the mass of free fine powder with a particle size less than 75 μm to the total mass of the dried sample. Granulation is stopped when the proportion of free fine powder is 2.00–15.00 wt%, and the wet particles in the granulation system are sent to the drying step.
[0022] Furthermore, the wet particles are dried using a fluidized bed with an inlet air temperature of 50–65°C and an outlet air temperature of 35–50°C. Drying is stopped when the drying loss of the wet particles is 1.50–4.00 wt%. The resulting dried particles are then granulated through a sieve with a mesh size of 0.80–1.50 mm. The granulated particles that have passed through the sieve are collected and used to mix with microcrystalline cellulose, colloidal silica, and magnesium stearate.
[0023] Furthermore, the dried and granulated polycarbohydrate calcium-pregelatinized starch porous bridging particles were fixed on the sample stage and sputter-coated with gold. Scanning electron microscopy was used to acquire images of the particle outer surface under the same magnification and image acquisition conditions, with at least 10 fields of view acquired for each sample. Polycarbohydrate calcium particles prepared without pregelatinized starch were used as control samples, and their outer surface images were acquired using the same sample processing method. Based on the image differences between the test sample and the control sample, the pregelatinized starch-covered area and the polycarbohydrate calcium-exposed area were marked. Image analysis software was used to calculate the projected area of the pregelatinized starch-covered area and the total projected area of the particle outer surface, and the projected area coverage rate was calculated according to the ratio of the two. The projected area coverage rate was recorded as a particle quality control parameter.
[0024] As another aspect of this invention, the present invention employs segmented granulation and subsequent total mixing and forming, primarily to achieve, fix, or amplify the aforementioned synergistic effects. In existing technologies, if only conventional dry mixing or direct tableting is relied upon, polycarboxymethyl calcium and excipients are prone to uneven local distribution due to differences in particle size, density, and surface state. Simply increasing the wet granulation strength may result in excessively dense particles, affecting disintegration and dispersion. This invention first forms porous bridged particles of polycarboxymethyl calcium-pregelatinized starch, then performs primary mixing with microcrystalline cellulose and colloidal silica, and finally adds magnesium stearate for short-term mixing, selecting tableting, encapsulation, or dispensing pathways. This ensures that the bridged particle structure is preserved before formulation formation. Furthermore, by controlling the mixing sequence and forming conditions, the adverse effects of excessive lubrication, excessive compaction, and particle segregation are reduced, thereby maintaining the synergistic relationship in the product formulation during the process.
[0025] Polycarboxymethyl calcium primarily serves as a high-content active ingredient and a water-absorbing and swelling agent. However, when it forms granules alone or in excessive amounts, it can lead to problems such as excessive fine powder, insufficient flowability, or localized dense formation after tableting due to the lack of a uniform bridging layer on the granule surface. Pregelatinized starch can participate in surface bridging and intergranular porosity regulation, but its addition alone or excessive coverage may increase intergranular adhesion and localized accumulation differences, affecting disintegration pathways and dosage distribution. This invention uses pregelatinized starch in combination with a dry-mix portion and an aqueous dispersion portion, or by dry-mixing all pregelatinized starch and then granulating it with purified water. This allows it to form an adjustable coating on the surface of polycarboxymethyl calcium granules. The particle size distribution is controlled by the addition method of the granulation solution, the proportion of free fine powder, the loss on drying, and the granulation sieve. This allows the bridging strength, surface coating, porosity retention, and the mixing state of the added excipients to mutually correct each other, ultimately achieving a balance between the inherently contradictory properties of processing flowability, dosage uniformity, mechanical strength, and disintegration performance.
[0026] Beneficial technical effects 1. This invention forms porous bridging particles by combining polycarboxylic acid calcium with pregelatinized starch, allowing the pregelatinized starch to form an adjustable coating on the particle surface. This reduces flow hindrance caused by the direct mixing of fine polycarboxylic acid calcium powder and avoids uneven distribution of excipients due to excessive particle growth, thereby improving the stability of formulation processing and the consistency of unit dosage.
[0027] 2. By controlling D50, projected area coverage, fine powder ratio, and free fine powder endpoint, this invention enables the wet bridging granulation process to have a clear quality control standard, and can establish a repeatable process window between granulation, drying, and granulation, reducing batch-to-batch fluctuations caused by relying solely on experience to judge the granulation endpoint.
[0028] 3. In this invention, microcrystalline cellulose, colloidal silica, and magnesium stearate are sequentially mixed with polycarbohydrate calcium-pregelatinized starch porous bridging particles. By utilizing the shaping support of microcrystalline cellulose, the flow regulation of colloidal silica, and the lubrication effect of magnesium stearate, the risks of tablet sticking, mixing segregation, and insufficient lubrication are reduced.
[0029] 4. In optional embodiments, the present invention introduces croscarmellose sodium and combines it with control of tableting main pressure, friability and disintegration time to ensure that the tablets maintain the necessary mechanical integrity during transportation and packaging, while forming a suitable disintegration and dispersion process in the use environment, thereby improving the contradiction between strength improvement and disintegration delay.
[0030] 5. The preparation method of the present invention can form different oral solid forms by tableting, capsule filling or dispensing. The key processes all use normal pressure, aqueous granulation solution and commercially available excipients, avoiding the introduction of complex organic solvents or dependence on special equipment, which is beneficial to subsequent scale-up production, quality control and dosage form adaptation. Attached Figure Description
[0031] Figure 1 The graph shows the effect of pregelatinized starch fraction on the RSD and disintegration time of polycarboxymethyl phosphate (PCP) calcium content.
[0032] Figure 2 The graph shows the effect of the amount of granulation solution added on the angle of repose and the RSD of polycarboxymethyl calcium content.
[0033] Figure 3 The graph shows the effect of drying weight loss on the angle of repose and friability.
[0034] Figure 4 The graph shows the effect of main compression pressure on friability and disintegration time.
[0035] Figure 5 The particle size distribution diagrams are for Example 1, Comparative Example 1, and Comparative Example 2.
[0036] Figure 6 The cumulative particle size distribution diagrams for Example 1, Comparative Example 1, and Comparative Example 2 are shown.
[0037] Figure 7 This is a comparison chart of the D50 and fine powder ratios for Example 1, Comparative Example 1, and Comparative Example 2.
[0038] Figure 8 The above is a statistical chart showing the projected area coverage of pregelatinized starch in Examples 1, 9, and 10.
[0039] Figure 9 This is a comparison chart of the mechanical integrity and disintegration time of Example 1, Comparative Example 5, and Comparative Example 8.
[0040] Figure 10 This is a comparison chart of powder flowability and dosage uniformity in Example 1, Comparative Example 7, and Comparative Example 11.
[0041] Figure 11 The chart shows the comparison of Hausner ratio and content RSD for Example 1, Comparative Example 7, and Comparative Example 11.
[0042] Figure 12 This is a comparison of macroscopic optical photographs of the final product of Example 1 and the final product of Comparative Example 11; wherein, Figure 12 Figure a in the image is a macroscopic optical photograph of the final product of Example 1; Figure 12 Figure b in the figure is a macroscopic optical photograph of the final product of Comparative Example 11.
[0043] Figure 13 The images show the SEM morphology and SEM surface scan comparison of the final product of Example 1 and the final product of Comparative Example 11; wherein, Figure 13 Figure a in the image is a low-magnification SEM image of the final product of Example 1; Figure 13 Figure b in the figure is a low-magnification SEM image of the final product of Comparative Example 11; Figure 13 Figure c in the image is a medium-magnification SEM image of the final product of Example 1; Figure 13 Image d in the figure is a medium-magnification SEM image of the final product of Comparative Example 11; Figure 13 Image e in the figure is a high-magnification SEM image of the final product of Example 1; Figure 13 Figure f in the figure is a high-magnification SEM image of the final product of Comparative Example 11; Figure 13 The g-image in the image is a SEM-EDS surface scan of the final product of Example 1; Figure 13 The h-figure in the image is a SEM-EDS surface scan of the final product of Comparative Example 11. Detailed Implementation
[0044] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Example 1
[0045] S1: Preparation target and raw material state This embodiment prepares a tablet form of polycarboxymethyl cellulose oral solid dosage form. Based on a theoretical total dosage form of 100.00 g, the components are: polycarboxymethyl cellulose 78.00 g, pregelatinized starch 6.24 g, microcrystalline cellulose 13.26 g, colloidal silica 0.20 g, magnesium stearate 0.30 g, and croscarmellose sodium 0.50 g. The residual moisture content of the particles, determined by loss on drying, is 1.50 g, and this is included in the theoretical total dosage form. The polycarboxymethyl cellulose, pregelatinized starch, microcrystalline cellulose, colloidal silica, magnesium stearate, and croscarmellose sodium are all pharmaceutical grade. All raw materials are commercially available or readily available.
[0046] S2: Preparation of porous bridged particles of polycarboxylic acid-pregelatinized starch Based on 100 parts by weight of polycarboxymethyl phosphate, 8 parts by weight of pregelatinized starch were taken, of which 3 parts by weight were used as the dry mixture and 5 parts by weight were used as the pregelatinized starch aqueous dispersion. 5 parts by weight of pregelatinized starch were added to 80 parts by weight of purified water and mechanically stirred at 300 rpm for 5 min at 20°C. The measured pH of the resulting pregelatinized starch aqueous dispersion was 5.0. 100 parts by weight of polycarboxymethyl phosphate and 3 parts by weight of pregelatinized starch were added to a high-shear granulator and mixed at low speed for 5 min under air atmosphere, normal pressure, and 20°C, followed by high-shear mixing for 1 min to obtain a dry-mixed powder. The pregelatinized starch aqueous dispersion was added to the dry-mixed powder in 4 portions, mixing at 300 rpm for 45 s after each addition, for a total granulation time of 3 min. The wet granules were sieved through a 0.80 mm sieve, and the wet granules that passed through the sieve were used as wet granules to be dried.
[0047] S3: Drying, granulation, and total compression tableting The wet granules to be dried were placed in a fluidized bed for drying. The inlet air temperature was 50℃, the outlet air temperature was 35℃, and the drying was carried out under normal pressure air atmosphere until the loss on drying was 1.50 wt%. The dried granules were sizing through a 0.80 mm sieve, and the sizing particles that passed through the sieve were collected. The polycarboxymethyl calcium-pregelatinized starch porous bridged granules, microcrystalline cellulose, and colloidal silica were put into a three-dimensional mixer and mixed for 5 min at 25℃ and 45% relative humidity. Then, magnesium stearate was added and mixed for 2 min to obtain the total mixture. The total mixture was compressed into tablets with a main compression pressure of 18 kN. The polycarboxymethyl calcium content in a single tablet was 800 mg, and the theoretical tablet weight was 1025.6 mg.
[0048] S4: Quality Inspection Methods and Results After granulation, the particles were subjected to laser diffraction particle size analysis using liquid paraffin as the dispersion medium, with the opacity controlled at 8%–12%, and the volume distribution D50 was recorded. Particles from the same batch were sieved through a 75 μm sieve to determine the proportion of fine powder. Gold-sprayed particles were imaged using a scanning electron microscope at the same magnification, and the projected area coverage was calculated. Tablets were tested according to the methods for evaluating tablet fragility and disintegration time. In this example, the D50 was 180 μm, the proportion of fine powder was 2.00 wt%, the projected area coverage was 30.00%, the tablet fragility was 0.10%, and the disintegration time was 18 min.
[0049] S5: Features and application scenarios of this embodiment This embodiment employs a scheme with high polycarboxylic acid calcium content, low pregelatinized starch ratio, low amount of pregelatinized starch aqueous dispersion, and high tableting pressure. The particle size is in the low value range, the particle surface coverage is low, and the tablet mechanical integrity is strong. It is suitable for tablet products that require a high per-tablet polycarboxylic acid calcium loading and emphasize transport tolerance. Example 2
[0050] Raw materials and proportions: In this embodiment, a tablet form of polycarboxymethyl cellulose oral solid dosage form was prepared. Based on a theoretical total dosage of 100.00 g, the following components were used: polycarboxymethyl cellulose 55.00 g, pregelatinized starch 13.75 g, microcrystalline cellulose 20.00 g, colloidal silica 1.00 g, magnesium stearate 1.50 g, and croscarmellose sodium 6.00 g. The residual moisture content of the particles, measured by loss on drying, was 2.75 g, and this was included in the theoretical total dosage. All raw materials were commercially available pharmaceutical grade or pharmaceutical excipient grade. Polycarboxymethyl cellulose and pregelatinized starch were sieved through a 0.80 mm sieve before feeding. Microcrystalline cellulose, colloidal silica, magnesium stearate, and croscarmellose sodium were equilibrated at 25°C and 45% relative humidity for 2 h before feeding.
[0051] Preparation process: Based on 100 parts by weight of polycarboxymethyl phosphate, 25 parts by weight of pregelatinized starch were taken, of which 5 parts by weight were used for dry mixing and 20 parts by weight were used to prepare a pregelatinized starch aqueous dispersion. 20 parts by weight of pregelatinized starch were added to 95 parts by weight of purified water and mechanically stirred at 500 rpm for 20 min at 35°C. The measured pH of the resulting pregelatinized starch aqueous dispersion was 7.5. 100 parts by weight of polycarboxymethyl phosphate and 5 parts by weight of pregelatinized starch were first mixed at low speed for 10 min under air atmosphere, normal pressure, and 35°C, and then mixed at high shear for 5 min to obtain a dry-mixed powder. The pregelatinized starch aqueous dispersion was added to the dry-mixed powder in three portions, mixing at 450 rpm for 80 s after each addition. The total wet bridging granulation time was 8 min. The wet granules were sieved through a 1.50 mm sieve and then proceeded to the drying step.
[0052] Post-processing: Wet granules were dried using a fluidized bed dryer at an inlet air temperature of 65℃ and an outlet air temperature of 50℃ until a drying loss of 2.75 wt% was achieved. The dried granules were then sizing using a 1.50 mm sieve, and the sizing particles were collected. Polycarboxymethyl cellulose (PCCF) calcium-pregelatinized starch porous bridged granules, microcrystalline cellulose, colloidal silica, and croscarmellose sodium were mixed for 20 min, followed by the addition of magnesium stearate and mixing for another 6 min to obtain the final mixture. The final mixture was then compressed into tablets at a main compression pressure of 6 kN, resulting in a PCCF calcium content of 300 mg per tablet and a theoretical tablet weight of 545.5 mg.
[0053] Quality inspection or performance testing After granulation, the D50, proportion of fine powder below 75 μm, scanning electron microscope projection area coverage, and loss on drying of the granules were measured. Tablets were also measured for friability and disintegration time. In this example, the D50 was 450 μm, the proportion of fine powder was 15.00 wt%, the projection area coverage was 75.00%, the tablet friability was 1.00%, and the disintegration time was 5 min.
[0054] Features of the solution in this embodiment This embodiment employs a scheme with low polycarboxylic acid calcium content, high pregelatinized starch ratio, high amount of pregelatinized starch aqueous dispersion, high surface coverage, and low tableting pressure. The particle size is in the high value range, and the content of added disintegrating components is high, making it suitable for tablet products that require rapid disintegration while also being able to be processed into tablets. Example 3
[0055] In this embodiment, the preparation object is a polycarboxymethyl cellulose oral solid dosage form in capsule-filled granule form. Based on a theoretical total dosage form of 100.00 g, the components are: polycarboxymethyl cellulose 66.00 g, pregelatinized starch 10.56 g, microcrystalline cellulose 15.04 g, colloidal silica 0.60 g, magnesium stearate 0.80 g, and croscarmellose sodium 3.00 g. The residual moisture content of the granules, measured by loss on drying, is 4.00 g, and this is included in the theoretical total dosage form. The polycarboxymethyl cellulose and pregelatinized starch are pharmaceutical grade, and all excipients are commercially available pharmaceutical grade raw materials.
[0056] Key parameters are as follows: based on 100 parts by mass of polycarboxymethyl calcium, 16 parts by mass of pregelatinized starch; 8 parts by mass of the pregelatinized starch are used as the dry mixture, and 8 parts by mass are mixed with 88 parts by mass of purified water to prepare a pregelatinized starch aqueous dispersion; the pregelatinized starch aqueous dispersion is dispersed at 30℃ for 12 min, and the measured pH value is 6.5; the dry mixture powder is first mixed at low speed for 7 min under air atmosphere and normal pressure, and then mixed at high shear for 3 min.
[0057] In the preparation process, 100 parts by weight of polycarboxymethyl calcium and 8 parts by weight of pregelatinized starch were first added to a high-shear granulator and mixed at 28°C to form a dry-mixed powder. Then, the pregelatinized starch aqueous dispersion was added to the dry-mixed powder in three separate additions, with a total granulation time of 5.5 min. During the granulation process, samples were taken every 90 s. After sieving through a 1.10 mm sieve, the wet granules that passed through the sieve were collected, dried, and then sieved through a 75 μm sieve to determine the proportion of free fine powder. Granulation was terminated when the proportion of free fine powder entered the control range of 2.00–15.00 wt%.
[0058] In post-processing, the wet granules were placed in a hot air circulating dryer and dried at 45°C under normal air pressure until the loss on drying was 4.00 wt%, then granulated through a 1.10 mm sieve. The granulated granules were mixed with microcrystalline cellulose, colloidal silica, and croscarmellose sodium for 12 min, followed by the addition of magnesium stearate and mixing for 4 min to obtain the final mixture. The final mixture was then filled into hard capsules, with each capsule containing 500 mg of polycarboxymethyl cellulose. The fill weight variation was monitored during the capsule filling process.
[0059] The quality testing methods and results were as follows: whole granules were subjected to laser diffraction particle size analysis, 75 μm sieving, scanning electron microscopy image projection area coverage analysis, and drying loss determination; capsule-filled granules were subjected to filler uniformity testing, and the total mixture of the same batch was compressed into evaluation tablets at 10 kN for comparison of friability and disintegration time in process studies. In this example, the D50 was 305 μm, the fine powder ratio was 8.00 wt%, the projection area coverage was 52.00%, the friability of the evaluation tablet was 0.45%, and the disintegration time of the evaluation tablet was 10.8 min.
[0060] This embodiment is applicable to capsule filling granules. The solution employs a moderate polycarboxylic acid calcium content, a moderate pregelatinized starch ratio, and high control of drying loss. The granules exhibit suitable filling and transferability, making it suitable for capsule formulation development that requires avoiding tableting while maintaining granule dispersibility. Example 4
[0061] I. Preparation Scale and Product Form: Polycarboxymethyl Calcium oral solid dosage form was prepared in granule form based on a theoretical total mass of 100.00 g. The raw materials included 70.00 g of polycarboxymethyl Calcium, 14.00 g of pregelatinized starch, 10.00 g of microcrystalline cellulose, 0.80 g of colloidal silica, 1.20 g of magnesium stearate, and 2.50 g of croscarmellose sodium. The residual moisture content of the granules, measured by loss on drying, was 1.50 g, and this was included in the theoretical total mass. All raw materials were pharmaceutical grade or pharmaceutical excipient grade, and were commercially available or purchased.
[0062] II. Construction of Bridged Particles: Based on 100 parts by weight of polycarboxymethyl phosphate (PCPF) calcium, 20 parts by weight of pregelatinized starch were taken, of which 10 parts by weight were used for dry mixing and 10 parts by weight were used to prepare a pregelatinized starch aqueous dispersion. 10 parts by weight of pregelatinized starch were added to 90 parts by weight of purified water and stirred at 400 rpm for 10 min at 25°C. The measured pH of the resulting pregelatinized starch aqueous dispersion was 6.0. 100 parts by weight of PCPF calcium and 10 parts by weight of pregelatinized starch were first mixed at low speed for 9 min under air atmosphere, normal pressure, and 32°C, and then mixed at high shear for 4 min to obtain a dry-mixed powder. The pregelatinized starch aqueous dispersion was added to the dry-mixed powder in 5 portions, with a total granulation time of 7 min.
[0063] III. Sieving, Drying, and Granulation: During the granulation process, the wet granules are sieved through a 1.50 mm sieve. The wet granules that pass through the sieve are then fed into a fluidized bed for drying. The inlet air temperature of the fluidized bed is 60℃, and the outlet air temperature is 45℃. Drying is carried out until the weight loss is 1.50 wt%. After drying, the granules are sized through a 1.20 mm sieve, and the sized granules that pass through the sieve are collected.
[0064] IV. Final Mixing and Packaging: Polycarboxymethyl Calcium-Pregelatinized Starch Porous Bridged Granules were mixed with microcrystalline cellulose, colloidal silica, and croscarmellose sodium in a three-dimensional mixer for 20 min, followed by the addition of magnesium stearate and mixing for 6 min to obtain the final mixture. The final mixture was then packaged into granules containing 600 mg of polycarboxymethyl Calcium for oral administration.
[0065] V. Quality Testing Methods and Results: Whole granules were used to determine D50, the proportion of fine powder below 75 μm, projected area coverage, loss on drying, and packaging weight variation. The same batch of total mixture was pressed into evaluation tablets at 12 kN for comparison of friability and disintegration time in process studies. In this example, D50 was 430 μm, the proportion of fine powder was 5.00 wt%, the projected area coverage was 70.00%, the friability of the evaluation tablet was 0.55%, and the disintegration time was 8.8 min.
[0066] VI. Process characteristics and application directions of this embodiment: This embodiment adopts medium-high calcium content of polycarbohydrate, medium-high pregelatinized starch ratio, long main mixing time and packaging method, with high surface coverage of granules and sufficient distribution of excipients. It is suitable for the development of granules that require dosage packaging and emphasize granule flowability and ease of administration.
[0067] Comparative Example 1: This example is essentially the same as Example 1, except that, based on 100 parts by weight of polycarboxymethyl phosphate, the amount of pregelatinized starch is changed to 5 parts by weight. Of these 5 parts by weight, 5 parts by weight are used to prepare the pregelatinized starch aqueous dispersion. No pregelatinized starch portion is used for dry mixing. The resulting pregelatinized starch aqueous dispersion is added to the dry-mixed powder in four separate additions. Except for the above differences, the remaining raw material composition, granulation, drying and granulation, total mixing, and tableting conditions are the same as in Example 1.
[0068] Comparative Example 2: This example is essentially the same as Example 1, except that, based on 100 parts by weight of polycarboxymethyl calcium, the amount of pregelatinized starch is changed to 30 parts by weight, of which 25 parts by weight are used for dry mixing and 5 parts by weight are used to prepare the pregelatinized starch aqueous dispersion. The resulting pregelatinized starch aqueous dispersion is then added to the dry-mixed powder in four separate additions. Except for the above differences, the remaining raw material composition, granulation, drying and granulation, total mixing, and tableting conditions are the same as in Example 1.
[0069] Comparative Example 3: This example is essentially the same as Example 1, except that 8 parts by weight of pregelatinized starch were dry-mixed with 100 parts by weight of polycarboxymethyl phosphate. The granulation solution was purified water, added in 3 separate additions of 6.00 wt% of the total mass of polycarboxymethyl phosphate and pregelatinized starch, in 3 separate additions of 2.00 wt%. Except for the granulation solution route and dosage, the granulation temperature, granulation time, drying and granulation, and overall mixing and tableting conditions were identical to those in Example 1.
[0070] Comparative Example 4: This example is essentially the same as Example 1, except that 8 parts by weight of pregelatinized starch were dry-mixed with 100 parts by weight of polycarboxymethyl phosphate. The granulation solution was purified water, added in 4 batches of 5.50 wt% of the total mass of polycarboxymethyl phosphate and pregelatinized starch, at a rate of 22.00 wt% of the total mass of the purified water. Except for the granulation solution route and dosage, the granulation temperature, granulation time, drying and granulation, and overall mixing and tableting conditions were identical to those in Example 1.
[0071] Comparative Example 5: Basically the same as Example 1, except that the fluidized bed drying endpoint was changed to a drying loss of 0.80 wt%. Except for the drying endpoint, the other raw material composition, granulation, granulation, total mixing and tableting conditions were the same as in Example 1.
[0072] Comparative Example 6: Basically the same as Example 1, except that the granulation screen for drying particles was changed to 2.00 mm. Except for the granulation screen, the other raw material composition, granulation, drying, total mixing and tableting conditions were the same as in Example 1.
[0073] Comparative Example 7: Basically the same as Example 1, except that the amount of colloidal silica was changed to 0.05 g. Except for the amount of colloidal silica, the other raw material composition, granulation, drying and granulation, and total mixing and tableting conditions were the same as in Example 1.
[0074] Comparative Example 8: Basically the same as Example 1, except that the main compression pressure was changed to 22 kN. Except for the main compression pressure, the other raw material composition, granulation, drying and granulation and total mixing conditions were the same as in Example 1.
[0075] Comparative Example 9: Essentially the same as Example 1, except that pregelatinized starch was not added; instead, 100 parts by weight of polycarboxymethyl phosphate and purified water were used for wet granulation. The purified water was added in four portions, each containing 2.00 wt% of the polycarboxymethyl phosphate, at a rate of 8.00 wt%. Except for the absence of pregelatinized starch and the use of purified water for granulation, all other drying, granulation, mixing, and tableting conditions were the same as in Example 1. This comparative example was used to investigate the synergistic relationship between polycarboxymethyl phosphate and pregelatinized starch.
[0076] Comparative Example 10: Essentially the same as Example 1, except that the pregelatinized starch aqueous dispersion preparation step was omitted. 8 parts by weight of pregelatinized starch were dry-mixed with 100 parts by weight of polycarboxymethyl phosphate, and the granulation solution was replaced with purified water. The amount of purified water added was 8.00 wt% of the total mass of polycarboxymethyl phosphate and pregelatinized starch, added in 4 separate 2.00 wt% batches. Except for the granulation solution route, the granulation, drying, granulation, mixing, and tableting conditions were the same as in Example 1. This comparative example was used to examine the synergistic relationship between the dry-mixed pregelatinized starch portion and the aqueous dispersion portion.
[0077] Comparative Example 11: Essentially the same as Example 1, except that the wet bridging granulation and fluidized bed drying steps were omitted. 78.00 g of polycarboxymethyl cellulose (PCCF), 6.24 g of pregelatinized starch, 13.26 g of microcrystalline cellulose, 0.20 g of colloidal silica, and 0.50 g of cross-linked sodium carboxymethyl cellulose were directly mixed for 5 min, followed by the addition of 0.30 g of magnesium stearate and mixing for 2 min before tableting. Other key conditions were maintained as follows: PCCF to pregelatinized starch mass ratio 100:8, tableting pressure 18 kN, PCCF content per tablet 800 mg, production environment 25°C, relative humidity 45%, and ambient air pressure. This comparative example was used to investigate the synergistic relationship between the PCCF-pregelatinized starch porous bridging particles and the sequential mixing of excipients.
[0078] Characterization and performance testing: The particle size distribution and fine powder ratio of polycarboxylated non-calcium pregelatinized starch porous bridging particles were tested to evaluate the effect of particle size distribution on flowability and dosage uniformity. Particle size was determined using laser diffraction according to GB / T 19077-2024 "Laser Diffraction Method for Particle Size Analysis". The samples were dispersed in liquid paraffin with an opacity of 8%–12%, and D10, D50, and D90 were recorded. Another sample was sieved through a 75 μm sieve to calculate the fine powder ratio, n≥3, and the mean and standard deviation were output.
[0079] Scanning electron microscopy (SEM) images and projected area coverage analysis were performed on porous bridging particles of polycarboxylated calcium-pregelatinized starch to evaluate the bridging coverage of pregelatinized starch on the surface of polycarboxylated calcium particles. Samples were fixed on the sample stage and sputtered with gold. At least 10 fields of view were acquired under the same magnification and image acquisition conditions. Polycarboxylated calcium particles without pregelatinized starch were used as image controls. The projected area coverage was calculated as the ratio of the projected area of the pregelatinized starch-covered area to the total projected area of the outer surface of the particles.
[0080] The powder flowability and packing behavior of the total mixture were tested to evaluate the effects of particle size, fine powder ratio, and colloidal silica content on processing transfer and filling stability. The angle of repose of the sample was measured by the funnel method, and the bulk density and tap density were determined. The Hausner ratio was calculated. The test temperature was 25°C and the relative humidity was 45%. Each batch was tested at least 3 times, and the mean and standard deviation were calculated. The angle of repose and Hausner ratio were obtained from the experiment. The units are ° and dimensionless, respectively. The lower the value, the better the flowability.
[0081] The purpose of friability testing on tablets or evaluation tablets made from the same batch of mixtures is to evaluate the influence of bridging particles and main compression pressure on mechanical integrity. Following the apparatus and judgment method of General Rule 0923 of the 2025 edition of the Chinese Pharmacopoeia for the test of tablet friability, a specified number of tablets are taken, free powder is removed and weighed, and then placed in a friability tester and rotated 100 times at 25 r / min. After removing the powder again, the tablets are weighed and the percentage of weight loss is calculated. n≥3. The friability is obtained from the experiment, and the unit is %. The lower the value, the better the wear resistance.
[0082] The purpose of disintegration time testing on tablets or evaluation tablets made from the same batch of total mixture is to evaluate the effects of bridging strength, cross-linked sodium carboxymethyl cellulose, and compression conditions on the dispersion process after administration. Following the principle of the lift-type disintegrator in General Rule 0921 of the 2025 edition of the Chinese Pharmacopoeia, the medium was water at 37℃±1℃. Six tablets were tested, and the time for complete disintegration without hardening was recorded. n≥3. The disintegration time was obtained from the experiment and the unit was min. It was used to compare the disintegration performance of different samples under the same test conditions.
[0083] The purpose of testing the uniformity of polycarboxymethyl calcium content in the formulation units was to evaluate whether the differences in particle size and packing between the particles and the excipients caused fluctuations in unit dose. Ten formulation units were randomly selected from each batch, and polycarboxymethyl calcium was released by acidification dispersion. The converted content of polycarboxymethyl calcium was then calculated using a methodologically validated calcium content determination method. The average content, standard deviation, and relative standard deviation were recorded. For n≥3, the RSD of polycarboxymethyl calcium content was obtained from the experiment. The lower the value, the better the dose uniformity.
[0084] To verify the synergistic improvement effect of this invention on processing flowability, dosage uniformity, mechanical strength and disintegration performance in high-content polycarboxylic acid calcium oral solid dosage forms, a single-factor investigation was first conducted on key formulation and process factors based on the formulation composition and preparation process of Example 1. Figure 1 This diagram illustrates the effect of the amount of pregelatinized starch on the RSD and disintegration time of polycarboxymethyl calcium (PCCMP). While keeping the PCCMP dosage, other formulation components, and process conditions constant, only the amount of pregelatinized starch was varied, with comparisons made at 5, 8, 12, 16, 20, 25, and 30 parts by weight. The results show that when the amount of pregelatinized starch is low, PCCMP is difficult to effectively disperse and bridge in the system, resulting in a higher RSD and unstable disintegration. When the amount of pregelatinized starch is too high, the increased proportion of excipients may lead to a decrease in particle dispersion and tablet uniformity. When the amount of pregelatinized starch is controlled at approximately 12–20 parts by weight, the RSD can be stabilized at approximately 2.2%–2.4%, and the disintegration time is approximately 11.2–12.5 min, indicating that an appropriate amount of pregelatinized starch can help improve dosage uniformity and disintegration performance.
[0085] Based on the established effect of pregelatinized starch on particle structure, the influence of wet granulation process on particle flowability and uniform distribution of active pharmaceutical ingredient was further investigated. Figure 2 The graph shows the effect of the amount of granulating solution added on the angle of repose and the RSD of polycarboxymethyl calcium content. With purified water as the granulating solution and other formulation and process conditions remaining constant, gradients of 6, 8, 10, 13, 16, 18, and 22 wt% were set. The results show that when the amount of granulating solution added is too low, the powder is insufficiently wetted and granulated, with particles remaining mainly in a loose powder state. The angle of repose can reach approximately 45.0°, and the RSD is approximately 8.0%, which is detrimental to the stability of subsequent tableting and filling. When the amount of granulating solution added is too high, the particles become too wet or locally agglomerate. Although the flowability may improve somewhat, the uniformity of the active ingredient distribution decreases. When the amount of granulation solution added is controlled at about 10–16 wt%, the angle of repose is about 30.2°–34.0° and the content RSD is about 2.5%–3.0%, indicating that an appropriate amount of granulation solution can promote the formation of a stable granule skeleton between polycarboxylic acid calcium and pregelatinized starch, while avoiding excessive densification or local agglomeration, thus taking into account both flowability and dosage uniformity.
[0086] After wet-process bridging particle formation, the particle drying endpoint directly affects residual moisture, particle compressibility, and tablet mechanical integrity. Figure 3 The diagram illustrates the effect of drying loss on angle of repose and friability in this method. Using Example 1 as a baseline, only the moisture content at the drying endpoint was varied, with drying loss gradients of 0.8, 1.5, 2.0, 2.8, 3.4, 4.0, and 4.8 wt%. The results show that over-drying increases particle friability and decreases compressibility. At a drying loss of approximately 0.8 wt%, tablet friability can increase to approximately 1.60%. Conversely, excessive residual moisture enhances particle adhesion, reduces flowability, and consequently increases the angle of repose. When the drying loss is controlled at approximately 1.5–4.0 wt%, the friability is approximately 0.10%–0.62%, and the angle of repose remains consistently between approximately 31.6° and 37.8°. This indicates that appropriate residual moisture is beneficial for maintaining interparticle bonding and tableting stability without significantly sacrificing processing flowability.
[0087] Furthermore, the main compression pressure during the tablet forming stage determines the degree of compaction of the particle skeleton and the state of tablet pore retention. Figure 4This diagram illustrates the effect of the main compression pressure on friability and disintegration time in this formulation. Using Example 1 as a baseline, only the main compression pressure was varied, with gradients of 4, 6, 9, 12, 15, 18, and 22 kN. The results show that when the main compression pressure is too low, the interparticle bonding is insufficient, with a friability of approximately 1.50% at 4 kN, indicating insufficient tablet breakage resistance. When the main compression pressure is too high, the tablet pores are excessively compressed, extending the disintegration time to approximately 25.0 min at 22 kN, which is detrimental to post-administration dispersion. When the main compression pressure is controlled within the range of approximately 9–18 kN, especially within the range of 12–18 kN, the friability can be reduced to approximately 0.10%–0.28%, and the disintegration time to approximately 11.0–18.0 min, indicating that a moderate degree of compaction can achieve a reasonable balance between tablet mechanical strength and disintegration performance.
[0088] The above single-factor results indicate that this approach does not simply rely on increasing the proportion of excipients or increasing the tableting pressure to improve formability, but rather regulates the particle structure through formulation bridging, wet granulation, appropriate drying, and reasonable tableting. To further illustrate the impact of particle size distribution on processing performance, Figure 5 This is a particle size distribution diagram of the key sample in this scheme, comparing the particle size distribution of Example 1, Comparative Example 1, and Comparative Example 2. The particle size distribution peak of Example 1 is concentrated in the medium particle size range, with a D50 of approximately 180 μm, and the distribution curve is relatively concentrated. Comparative Example 1 has a finer particle size, with a D50 of approximately 145 μm, and a significant increase in the distribution of fine powder ends. Comparative Example 2 has a coarser particle size, with a D50 of approximately 505 μm, and an increased proportion of coarse particles. These results indicate that excessively fine particle size easily leads to powder agglomeration, adsorption, and decreased flowability, while excessively coarse particle size may cause mixing stratification and dosage fluctuations. The medium-sized particles formed in Example 1 are more conducive to subsequent stable filling and tableting.
[0089] Figure 6 This is a cumulative particle size distribution diagram of the key samples in this scheme, further demonstrating the cumulative undersize distribution changes of Example 1, Comparative Example 1, and Comparative Example 2. The cumulative distribution curve of Example 1 is smooth, and the particle size transition is relatively concentrated, with a D50 of approximately 180 μm, indicating continuous particle gradation and controllable distribution. The cumulative proportion of Comparative Example 1 increases rapidly in the low particle size region, indicating a high content of fine powder. The cumulative curve of Comparative Example 2 shifts significantly towards the larger particle size direction, indicating an increase in the proportion of coarse particles. These results further demonstrate from the perspective of cumulative distribution that the particle composition of Example 1 can avoid the two extreme states of excessive fine powder and excessive coarse particles, which is conducive to maintaining relatively stable powder flow and active ingredient distribution.
[0090] Figure 7This chart compares the D50 and fine powder ratio of key samples in this scheme, quantitatively comparing the median particle size and fine powder ratio of Example 1, Comparative Example 1, and Comparative Example 2. Example 1 has a D50 of approximately 180 μm and a fine powder ratio of approximately 2.0 wt%; Comparative Example 1 has a D50 of approximately 145 μm, but the fine powder ratio increases to approximately 18.0 wt%; Comparative Example 2 has a D50 of approximately 505 μm, and although the fine powder ratio is lower, the particle size is significantly coarser. These results indicate that simply reducing the fine powder ratio or simply adjusting the median particle size is insufficient to achieve good process adaptability. Only when a moderate D50 and a low fine powder ratio coexist synergistically can the mixing uniformity, flowability, and tableting stability of the high-content polycarbohydrate calcium system be improved more effectively.
[0091] Based on the optimization of particle size distribution, the structural role of pregelatinized starch is further explained by the particle surface coverage state. Figure 8 This chart shows the projected area coverage of pregelatinized starch in this scheme, comparing the coverage of pregelatinized starch on the surface of particles or powders in Example 1, Comparative Example 9, and Comparative Example 10. The projected area coverage of pregelatinized starch in Example 1 is approximately 30.0%, indicating that pregelatinized starch can form a sufficiently dense but not excessively dense bridging distribution on the surface and between polycarboxylic acid granules. Comparative Example 9, without the addition of pregelatinized starch, has a coverage rate close to 0%, making it difficult to form effective bridging. The coverage rate of Comparative Example 10 is approximately 18.0%, lower than that of Example 1, indicating relatively insufficient bridging and dispersion. These results demonstrate that proper coverage by pregelatinized starch does not involve forming a complete coating layer, but rather establishing multi-point connections and porous support structures between particles, thereby helping to improve particle binding capacity, content uniformity, and stability during disintegration.
[0092] To verify whether the above particle structure regulation can ultimately be transformed into the comprehensive performance advantages of tablets, the mechanical integrity, disintegration time, powder flowability, and dosage uniformity of tablets were further compared. Figure 9 This diagram compares the mechanical integrity and disintegration time of tablets from Example 1, Comparative Example 5, and Comparative Example 8. Example 1 showed a friability of approximately 0.10% and a disintegration time of approximately 18.0 min, indicating good resistance to breakage while maintaining acceptable disintegration performance. Comparative Example 5 showed a friability of approximately 1.60%, indicating a looser tablet structure and insufficient mechanical integrity. While Comparative Example 8 showed a friability of approximately 0.08%, its disintegration time was extended to approximately 25.0 min, indicating that excessive compaction or overly dense structure reduces dispersion efficiency. These results demonstrate that higher tablet strength is not always better. This method combines porous bridging particles with moderate compaction to achieve a more reasonable balance between resistance to breakage and disintegration performance.
[0093] Figure 10This diagram compares the powder flowability and dosage uniformity of this formulation, comparing the angle of repose and RSD of polycarboxylic acid calcium content in Example 1, Comparative Example 7, and Comparative Example 11. The angle of repose in Example 1 is approximately 37.8°, and the RSD is approximately 3.8%; the angle of repose in Comparative Example 7 is approximately 42.0°, and the RSD is approximately 5.5%; the angle of repose in Comparative Example 11 is approximately 50.0°, and the RSD is approximately 10.0%. The results indicate that decreased flowability leads to fluctuations in tablet filling and uneven mixing distribution, thus significantly increasing the RSD of the active pharmaceutical ingredient content. Example 1, through particle size control, wet bridging granulation, and synergistic adjustment of excipients, effectively reduced powder flow resistance and made the dosage distribution of high-content polycarboxylic acid calcium in solid dosage forms more stable.
[0094] Figure 11 This graph compares the Hausner ratio and content RSD of this scheme, further evaluating the processing adaptability of different samples from the perspective of packing flowability. The Hausner ratio of Example 1 is approximately 1.22, and the content RSD is approximately 3.8%; the Hausner ratio of Comparative Example 7 is approximately 1.32, and the content RSD is approximately 5.5%; the Hausner ratio of Comparative Example 11 is approximately 1.48, and the content RSD is approximately 10.0%. An increased Hausner ratio generally reflects enhanced powder compressibility and decreased free flowability. The increase in content RSD with increasing Hausner ratio in the graph indicates a consistency between flowability indicators and dosage uniformity. Example 1 significantly outperformed the control samples with direct mixing or insufficient structural regulation in both Hausner ratio and content RSD, further demonstrating that wet-bridged particle pre-structuring helps improve the processing stability of high-drug-loaded systems.
[0095] To visually demonstrate how these performance differences manifest in the final tablet appearance, Figure 12 The image shows a macroscopic optical photograph comparison between the final product of Example 1 and the final product of Comparative Example 11, used to compare the appearance integrity of polycarboxylic acid calcium tablets obtained by wet-bridged granulation and tableting versus direct mixing and tableting. Figure 12 a is a macroscopic optical photograph of the final product of Example 1. This sample was prepared by wet bridging granulation of polycarbohydrate calcium-pregelatinized starch, fluidized bed drying, 0.80 mm granulation, and 18 kN tableting. The content of polycarbohydrate calcium per tablet is 800 mg, and the theoretical tablet weight is 1025.6 mg. The tablets have an intact appearance, regular edges, and uniform surface, indicating that the pre-structured particle skeleton can withstand the tableting process and maintain the macroscopic integrity of the tablets. Figure 12b is a macroscopic optical photograph of the final product of Comparative Example 11. This sample omits the wet bridging granulation and fluidized bed drying steps and is prepared by direct mixing and tableting. The formulation composition and the 18 kN tableting main pressure are consistent with those of Example 1. Its appearance uniformity and edge integrity are different from those of Example 1, indicating that relying solely on direct mixing and mechanical compaction is insufficient to fully solve the forming stability problem of high-content polycarbohydrate non-calcium systems. The wet bridging particle pre-structuring step improves the appearance and structural integrity of the tablets.
[0096] Figure 13 The images show the SEM morphology and SEM surface scan comparison of the final product of Example 1 and the final product of Comparative Example 11, which are used to further illustrate the regulatory effect of wet bridging granulation on the particle skeleton, bridging structure and elemental spatial distribution from a microscopic level. Figure 13 Image a is a low-magnification SEM image of the final product of Example 1. It can be seen that the polycarboxylic acid-pregelatinized starch porous bridging particle group formed after granulation at 0.80 mm has a particle D50 of about 180 μm after granulation, indicating that Example 1 can form a particle skeleton with moderate size and relatively controllable distribution. Figure 13 b is a low-magnification SEM image of the final product of Comparative Example 11, showing the compacted powder area in the cross-section of the tablet after direct mixing and compression. It lacks a clear porous bridging particle group, indicating that the particle structure is difficult to be effectively established before tableting after the wet bridging granulation is cancelled.
[0097] Further observation of the morphology at medium and high magnification SEM levels can further clarify the structural differences between the two. Figure 13 c is a medium-magnification SEM image of the final product of Example 1, showing the outline of single or a few particles, interparticle pores, and local bridging regions, indicating that the pregelatinized starch dry mix and the aqueous dispersion can synergistically promote interparticle bridging. Figure 13 Image d is a medium-magnification SEM image of the final product of Comparative Example 11. It shows the particle contact interface and local discontinuous areas after the raw materials and excipients are directly compacted, indicating that the bonding between particles mainly depends on mechanical compaction during the tableting process and lacks a stable bridging network. Figure 13 e is a high-magnification SEM image of the final product of Example 1, showing that there are local low-coverage bridging structures, rough pores and compacted interfaces on the particle surface. The projected area coverage of the pregelatinized starch is about 30.00%, indicating that Example 1 does not form a dense coating, but rather a porous bridging structure with both bonding points and pore channels. Figure 13 f is a high-magnification SEM image of the final product of Comparative Example 11, showing the characteristics of directly compacted powder boundaries, local pores or cracks, further illustrating that Comparative Example 11 lacks the stable, continuous and controllable bridging points and porous particle surface structure of Example 1.
[0098] At the level of element distribution, Figure 13g is the SEM-EDS surface scan of the final product of Example 1. The elemental channels include Ca, O, C, Si, Na, and Mg, used to show the spatial correspondence between the Ca-enriched particle framework and the low-content excipient elements. The results show that the polycarboxymethyl phosphate matrix structure and excipient components in Example 1 have good spatial synergy within a large field of view, indicating that wet bridging granulation can promote the rational distribution of the active pharmaceutical ingredient and excipients in the particle framework. Figure 13 h represents the SEM-EDS surface scan of the final product of Comparative Example 11, using the same Ca, O, C, Si, Na, and Mg element channels as in Example 1, to compare and show the differences in Ca-rich regions and low-content excipient element distribution in the directly mixed tablet samples. Compared to Example 1, Comparative Example 11 exhibits relatively insufficient particle skeleton continuity and elemental distribution uniformity, indicating that wet bridging granulation not only improves macroscopic formation but also optimizes particle connection methods and excipient spatial distribution at the microscale.
[0099] In conclusion, Figures 1 to 4 This indicates that there are reasonable control ranges for the amount of pregelatinized starch, the amount of granulation solution added, the loss on drying, and the main compression pressure, which can balance the uniformity of dosage, flowability, mechanical strength, and disintegration performance. Figures 5 to 8 This further indicates that medium particle size, low fine powder ratio, and moderate pregelatinized starch coating are conducive to the formation of porous bridged particle structures; Figures 9 to 11 From the perspectives of tablet performance and powder science indicators, this structure can simultaneously improve mechanical integrity, disintegration properties, flowability, and content uniformity. Figure 12 and Figure 13 The practical effects of wet-process bridging particle pre-structuring are demonstrated from the perspectives of macroscopic appearance, microscopic morphology, and elemental distribution. Thus, this invention addresses the difficulty of simultaneously addressing the issues of insufficient flowability, dose fluctuation, insufficient strength, and slow disintegration in high-content polycarboxylic acid calcium oral solid dosage forms. It establishes a continuous improvement path from formulation structure, particle size distribution, granulation process to tablet performance, achieving a synergistic balance between processing stability and post-administration dispersibility.
[0100] Table 1 Performance of Examples and Comparative Examples
[0101] As can be seen from the performance of the examples and comparative examples in Table 1, Examples 1–4 show a relatively balanced trend among D50, fine powder ratio, projected area coverage, angle of repose, content RSD, friability, and disintegration time. In the conventional comparative examples, deviations in the amount of pregelatinized starch, the amount of granulation solution added, the loss on drying, the granulation sieve, colloidal silica, and the main compression pressure usually only improve one indicator or cause another indicator to deteriorate. In the synergistic comparative examples, the absence of pregelatinized starch, the elimination of the aqueous dispersion, or the elimination of porous bridging granulation all showed an unfavorable trend in projected area coverage, flowability, content uniformity, and mechanical integrity, indicating that the data logic corresponds to the balance between processing flowability and dosage uniformity, and mechanical strength and disintegration performance.
[0102] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.
Claims
1. A polycarboxymethyl calcium oral solid dosage form, characterized in that, Including polycarboxylic acid calcium-pregelatinized starch porous bridging particles, microcrystalline cellulose, colloidal silica and magnesium stearate; The polycarboxylic acid calcium-pregelatinized starch porous bridging particles include polycarboxylic acid calcium and pregelatinized starch. In the polycarboxymethyl calcium-pregelatinized starch porous bridging particles, the mass ratio of polycarboxymethyl calcium to pregelatinized starch is 100:8–25. The D50 of the polycarbohydrate calcium-pregelatinized starch porous bridged particles is 180–450 μm, and the projected area coverage of the pregelatinized starch on the surface of the polycarbohydrate calcium particles is 30.00–75.00%. In the aforementioned polycarboxymethyl calcium oral solid dosage form, the content of polycarboxymethyl calcium is 55.00–78.00 wt% based on the total mass of the polycarboxymethyl calcium oral solid dosage form.
2. The polycarboxylic acid calcium oral solid dosage form according to claim 1, characterized in that, The polycarbohydrate-calcium-pregelatinized starch porous bridged particles are prepared by the following steps: A1. Raw material preparation: Take 100 parts by weight of polycarboxymethyl calcium and 8–25 parts by weight of pregelatinized starch; A2. Dry mixing: The polycarboxymethyl calcium is mixed with the portion of the pregelatinized starch used for dry mixing to obtain a dry-mixed powder; A3. Wet bridging granulation: Granulation solution is added to the dry-mixed powder to granulate it and wet granules are obtained. A4. Post-processing: The wet granules are dried and granulated to obtain the polycarboxylic acid calcium-pregelatinized starch porous bridged granules.
3. The polycarboxylic acid calcium oral solid dosage form according to claim 2, characterized in that, In step A2, the polycarboxymethyl calcium and the portion of the pregelatinized starch used for dry mixing are mixed in an air atmosphere for 5–15 min. In step A3, the granulation solution is a pregelatinized starch aqueous dispersion, which is obtained by dispersing 5–20 parts by weight of pregelatinized starch that was not used in the dry mixing in step A2 with 80–95 parts by weight of purified water at 20–35°C for 5–20 min. The pH value of the pregelatinized starch aqueous dispersion is 5.0–7.5, and all of the pregelatinized starch aqueous dispersion is added to the dry-mixed powder. The granulation conditions are 20–35°C and normal pressure, and the granulation time is 3–8 min. In step A4, the wet granules are dried at 45–65°C until the weight loss is 1.50–4.00 wt%, and then granulated through a 0.80–1.50 mm sieve. The proportion of fine powder smaller than 75 μm in the obtained polycarboxy-calcium-pregelatinized starch porous bridged particles was 2.00–15.00 wt%.
4. The polycarboxylic acid calcium oral solid dosage form according to claim 2, characterized in that, In step A3, all of the pregelatinized starch is used for dry mixing in step A2. The granulation solution is purified water, and the total amount of purified water added is 8.00–18.00 wt% of the total mass of polycarboxymethyl phosphate and pregelatinized starch. The purified water is added in several portions, with each addition being 2.00–6.00 wt% of the total mass of polycarboxymethyl phosphate and pregelatinized starch. The granulation endpoint is defined as a free fine powder ratio of less than 75 μm, measured after drying of the sampled wet granules, being 2.00–15.00 wt%.
5. The polycarboxylic acid calcium oral solid dosage form according to claim 1, characterized in that, The microcrystalline cellulose in the polycarboxymethyl cellulose oral solid dosage form is 5.00–20.00 wt%, the colloidal silica in the polycarboxymethyl cellulose oral solid dosage form is 0.20–1.00 wt%, the magnesium stearate in the polycarboxymethyl cellulose oral solid dosage form is 0.30–1.50 wt%, and the polycarboxymethyl cellulose oral solid dosage form further includes croscarmellose sodium in the polycarboxymethyl cellulose oral solid dosage form is 0.50–6.00 wt%, and the total content of polycarboxymethyl cellulose, pregelatinized starch, microcrystalline cellulose, colloidal silica, magnesium stearate and croscarmellose sodium in the polycarboxymethyl cellulose oral solid dosage form is not greater than 100 wt% based on the total mass of the polycarboxymethyl cellulose oral solid dosage form.
6. The polycarboxylic acid calcium oral solid dosage form according to claim 1, characterized in that, The polycarboxymethyl calcium oral solid dosage form is a tablet, capsule-filled granule, or granule; when the polycarboxymethyl calcium oral solid dosage form is a tablet, the content of polycarboxymethyl calcium in a single tablet is 300–800 mg.
7. A method for preparing a polycarboxymethyl calcium oral solid dosage form as described in any one of claims 1-6, characterized in that, Includes the following steps: S1. Provides polycarbohydrate calcium-pregelatinized starch porous bridged granules made from polycarbohydrate calcium and pregelatinized starch through raw material preparation, dry mixing, wet bridging granulation, drying and granulation. S2. Mix the polycarboxymethyl calcium-pregelatinized starch porous bridging particles with microcrystalline cellulose and colloidal silica for 5–20 min, then add magnesium stearate and mix for 2–6 min to obtain the total mixture; S3. Compress the total mixture into tablets, capsules, or dispense to obtain the polycarboxymethyl calcium oral solid dosage form.
8. The preparation method according to claim 7, characterized in that, In step S1, the dry mixing of the polycarboxymethyl calcium and the portion of the pregelatinized starch used for dry mixing is first performed at a low speed for 5–10 min, and then at a high shear rate for 1–5 min.
9. The preparation method according to claim 7, characterized in that, In step S2, the amount of colloidal silica added is 0.20–1.00 wt% of the total mixture, and the amount of magnesium stearate added is 0.30–1.50 wt% of the total mixture.
10. The preparation method according to claim 7, characterized in that, When step S3 is tableting, the main tableting pressure is 6–18 kN, the resulting tablets have a friability of 0.10–1.00% and a disintegration time of 5–18 min.
Citation Information
Patent Citations
Polycarbophil calcium tablet and preparation method thereof
CN112704664A